Cohort Profile: The Chinese Ovarian Aging Cohort (COACH) - Changjing Wang; Tingting Meng; Wei Luo; Jiangtao Zhang; Yongzhi Cao; Cheng Li; Jing Zhang; Xuan Gao; Peihao Liu; Chenxi Li; Dongshan Zhu; Tao Zhang; et al. (Phenomics, 2026)

Effects of Continuous Grafting on the Growth and Selenium Accumulation Characteristics in the Post-Generations of Tomato - Shiling Meng; Xiaoli Song; Wende Zhou; Juan Huang; Yatian Zhao; Wanjia Tang; Yi Tang; Bo Sun; Huanxiu Li; Zhi Huang (Journal of Soil Science and Plant Nutrition, 2025)

Evolving Therapeutic Landscape of Intracerebral Hemorrhage: Emerging Cutting-Edge Advancements in Surgical Robots, Regenerative Medicine, and Neurorehabilitation Techniques - Danyang Chen; Zhixian Zhao; Shenglun Zhang; Shiling Chen; Xuan Wu; Jian Shi; Na Liu; Chao Pan; Yingxin Tang; Cai Meng; Xingwei Zhao; Bo Tao; et al. (Translational Stroke Research, 2025)
Intracerebral hemorrhage (ICH) is the most serious form of stroke and has limited available therapeutic options. As knowledge on ICH rapidly develops, cutting-edge techniques in the fields of surgical robots, regenerative medicine, and neurorehabilitation may revolutionize ICH treatment. However, these new advances still must be translated into clinical practice. In this review, we examined several emerging therapeutic strategies and their major challenges in managing ICH, with a particular focus on innovative therapies involving robot-assisted minimally invasive surgery, stem cell transplantation, in situ neuronal reprogramming, and brain-computer interfaces. Despite the limited expansion of the drug armamentarium for ICH over the past few decades, the judicious selection of more efficacious therapeutic modalities and the exploration of multimodal combination therapies represent opportunities to improve patient prognoses after ICH.

Recycling of flotation residual carbon from coal gasification fine slag through thermal combustion reaction: Insight into the spatial and temporal multi-scale evolution of typical heavy metals - Yang Guo; Jianjun Wu; Fanhui Guo; Yixin Zhang; Shiling Yuan; Chunan Du; Juan Chen; Meng Lin (Fuel, 2025)

Effects of Mutual Grafting on Fruit Quality in Post-grafting generation of Two Genotypes Cherry Tomato (Lycopersicon esculentum) - Zhi Huang; Shiling Meng; Huizhong Luo; Wende Zhou; Juan Huang; Yatian Zhao; Xiaoli Song; Yi Tang; Bo Sun; Huanxiu Li (Journal of Soil Science and Plant Nutrition, 2024)

Surgical Robotics for Intracerebral Hemorrhage Treatment: State of the Art and Future Directions - Zhuojin Wu; Danyang Chen; Chao Pan; Ge Zhang; Shiling Chen; Jian Shi; Cai Meng; Xingwei Zhao; Bo Tao; Diansheng Chen; Wenjie Liu; Han Ding; et al. (Annals of Biomedical Engineering, 2023)
Intracerebral hemorrhage (ICH) is a stroke subtype with high mortality and disability, and there are no proven medical treatments that can improve the functional outcome of ICH patients. Robot-assisted neurosurgery is a significant advancement in the development of minimally invasive surgery for ICH. This review encompasses the latest advances and future directions of surgical robots for ICH. First, three robotic systems for neurosurgery applied to ICH are illustrated. Second, the key technologies of robot-assisted surgery for ICH are introduced in aspects of stereotactic technique and navigation, the puncture instrument, and hematoma evacuation. Finally, the limitations of current surgical robots are summarized, and the possible development direction is discussed, which is named “multisensor fusion and intelligent aspiration control of minimally invasive surgical robot for ICH”. It is expected that the new generation of surgical robots for ICH will facilitate quantitative, precise, individualized, standardized treatment strategies for ICH.

Comparative transcriptomic insights into the mechanisms of electron transfer in Geobacter co-cultures with activated carbon and magnetite - Shiling Zheng; Fanghua Liu; Meng Li; Leilei Xiao; Oumei Wang (Science China Life Sciences, 2018)